The Impact of the European Community's internal Market on the EFTA : Occa Paper No.74. (Occasional Papers; Occasional Paper, 1990)
This paper provides an overview of the likely impact of the creation of the European Community (EC) internal market on the European Free Trade Association (EFTA) members. The focus is on the four freedoms and the institutional and legal changes required for increased economic cooperation between the EC and EFTA. Although not formally part of the negotiations, certain tax issues are also raised. The paper is in ten parts and includes a summary and glossary. The paper also discusses the institutional and legal changes that may prove necessary for greater EC-EFTA cooperation and the implications of the internal market for trade, production, and resource allocation in the EFTA countries. It examines issues related to trade in goods-mainly industrial goods-and transport services and considers issues of labor mobility and trade in financial services. Changes would also appear desirable in the areas of industrial and intellectual property rights-notably counterfeiting, trademarks, copyrights, and patents.